Electrode mixture, electrode and secondary battery

By using an electrode composition containing lithium transition metal oxide, conductive additive and fluorine-containing copolymer, the problem of insufficient adhesion of the electrode mixing layer to the current collector is solved, and the flexibility and battery performance of the battery are improved.

JP7626314B2Active Publication Date: 2025-02-07DAIKIN INDUSTRIES LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022512210
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-02
Filing Date
2021-03-29
Publication Date
2025-02-07
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

The electrode composition of the conventional non-aqueous electrolyte secondary battery is difficult to form an electrode mixing layer with good flexibility and adhesion to the current collector, resulting in poor battery performance.

Method used

An electrode composition containing lithium-containing transition metal oxides, conductive additives, fluorine-containing copolymers and organic solvents is used, wherein the conductive additives are multi-walled carbon nanotubes, carbon nanowires, carbon nanofibers and graphene, and the fluorine-containing copolymer contains more than 50 mol% vinylidene fluoride-based units for forming the electrode mixing layer.

Benefits of technology

The excellent flexibility and adhesion of the electrode mixing layer to the current collector is achieved, and the overall battery characteristics of the secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626314000001
    Figure 0007626314000001
  • Figure 0007626314000002
    Figure 0007626314000002
  • Figure 0007626314000003
    Figure 0007626314000003
Patent Text Reader

Abstract

Provided is an electrode mixture which contains a lithium-containing transition metal oxide, an auxiliary conductive agent, a binder and an organic solvent. The auxiliary conductive agent contains at least one type of nanocarbon material selected from the group consisting of multiwalled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes and graphenes. The binder contains a fluorine-containing copolymer that contains vinylidene fluoride units and fluorinated monomer units (excluding vinylidene fluoride units). The content of vinylidene fluoride units in the fluorine-containing copolymer is more than 50 mol% and not more than 99 mol% relative to the total amount of monomer units.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode mixture, an electrode, and a secondary battery. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries have a high voltage, high energy density, low self-discharge, low memory effect, and can be made extremely lightweight, and for these reasons, they are used in small, portable electric and electronic devices such as notebook computers, mobile phones, smartphones, tablet computers, and ultrabooks, and are also being put into practical use as a wide range of power sources, including on-board power sources for driving automobiles and large stationary power sources.

[0003] As an electrode mixture for forming an electrode included in such a non-aqueous electrolyte secondary battery, for example, Patent Document 1 discloses a composite positive electrode active material including a solvent, a positive electrode active material, and a first binder covering a surface of the positive electrode active material and insoluble in the solvent, a fibrous carbon material having an average fiber diameter of 40 nm or less and an average aspect ratio of 500 or more, and a second binder soluble in the solvent, wherein the mass % of the first binder relative to the total mass of the composite positive electrode active material is 0.2 to 1.5 mass %, the mass % of the fibrous carbon material relative to the total mass of all solid contents is 0.01 to 0.5 mass %, the mass % of the second binder relative to the total mass of all solid contents is 0.1 to 0.5 mass %, and the specific surface area of ​​the positive electrode active material is a(m 2 / g), and when the mass % of the first binder relative to the total mass of the composite positive electrode active material is b (mass %), b / a is 5.0 or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-182989 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide an electrode mixture that can form an electrode mixture layer that is excellent in flexibility and adhesion to a current collector, and can form a secondary battery that has excellent battery characteristics. [Means for solving the problem]

[0006] According to the present disclosure, there is provided an electrode mixture containing a lithium-containing transition metal oxide, a conductive assistant, a binder, and an organic solvent, wherein the conductive assistant contains at least one nanocarbon material selected from the group consisting of multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphenes, and the binder contains a fluorine-containing copolymer containing vinylidene fluoride units and fluorinated monomer units (excluding vinylidene fluoride units), and the content of vinylidene fluoride units in the fluorine-containing copolymer is more than 50 mol% and not more than 99 mol% with respect to all monomer units.

[0007] The nano-carbon material is preferably at least one selected from the group consisting of multi-walled carbon nanotubes and graphene. The content of vinylidene fluoride units in the fluorine-containing copolymer is preferably 57.0 mol % or more and 97.0 mol % or less based on the total monomer units. The fluorinated monomer unit is preferably a tetrafluoroethylene unit. The content of the binder is preferably 0.3 to 3.0% by mass with respect to the total mass of the lithium-containing transition metal oxide, the conductive assistant, and the binder. The content of the conductive assistant is preferably 0.3 to 3.0% by mass with respect to the total mass of the lithium-containing transition metal oxide, the conductive assistant, and the binder. It is preferable that the binder further contains polyvinylidene fluoride.

[0008] The present disclosure also provides an electrode including a current collector and an electrode mixture layer formed from the electrode mixture and provided on one or both sides of the current collector.

[0009] The present disclosure also provides a secondary battery including the above electrode. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide an electrode mixture that can form an electrode mixture layer that is excellent in flexibility and adhesion to a current collector, and can form a secondary battery that has excellent battery characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.

[0012] <Electrode mixture> The electrode mixture of the present disclosure contains a lithium-containing transition metal oxide, a conductive assistant, a binder, and an organic solvent.

[0013] <Lithium-containing transition metal oxide> The electrode mixture of the present disclosure contains a lithium-containing transition metal oxide. The lithium-containing transition metal oxide functions as a positive electrode active material or a negative electrode active material in the electrode mixture layer.

[0014] The electrode mixture of the present disclosure can be used as a positive electrode mixture when it contains a lithium-containing transition metal oxide that functions as a positive electrode active material, and can be used as a negative electrode mixture when it contains a lithium-containing transition metal oxide that functions as a negative electrode active material. In particular, the electrode mixture of the present disclosure is preferably a positive electrode mixture. That is, the electrode mixture of the present disclosure preferably contains a lithium-containing transition metal oxide as a positive electrode active material.

[0015] The transition metal of the lithium-containing transition metal oxide is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, or the like.

[0016] Examples of lithium-containing transition metal oxides that function as positive electrode active materials include lithium-cobalt composite oxides such as LiCoO2, lithium-nickel composite oxides such as LiNiO2, lithium-manganese composite oxides such as LiMnO2, LiMn2O4, and Li2MnO3, and those in which some of the transition metal atoms that are the main components of these lithium-containing transition metal oxides have been replaced with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, and Si. Specific examples of those that have been replaced include LiNi 0.5 Mn 0.5 O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn 1.8 Al 0.2 O4, LiMn 1.5 Ni 0.5 O4, Li4Ti5O 12 etc.

[0017] In addition, as the lithium-containing transition metal oxide functioning as the positive electrode active material, a lithium-containing transition metal phosphate compound can also be used. Specific examples of the lithium-containing transition metal phosphate compound include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, and LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium-containing transition metal phosphate compounds in which a part of the transition metal atoms that are the main components of these lithium-containing transition metal phosphate compounds is replaced with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, and Si.

[0018] As the lithium-containing transition metal oxide functioning as a positive electrode active material, lithium-nickel composite oxides are preferable, and the general formula (1): General formula (1): Li y Ni 1-x M x O2 (In the formula, x is 0.01≦x≦0.5, y is 0.9≦y≦1.2, and M represents a metal atom (excluding Li and Ni).) Lithium-nickel composite oxides represented by the following formula are more preferable. Lithium-containing transition metal oxides that contain a large amount of Ni are thus useful for increasing the capacity of secondary batteries.

[0019] In general formula (1), x is a coefficient satisfying 0.01≦x≦0.5, and since a secondary battery with a higher capacity can be obtained, it is preferable that 0.05≦x≦0.4, and more preferably 0.10≦x≦0.3.

[0020] In the general formula (1), examples of the metal atom of M include V, Ti, Cr, Mn, Fe, Co, Cu, Al, Zn, Mg, Ga, Zr, Si, etc. As the metal atom of M, transition metals such as V, Ti, Cr, Mn, Fe, Co, Cu, etc., or combinations of the above transition metals with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Mg, Ga, Zr, Si, etc. are preferred.

[0021] The lithium-containing transition metal oxide that functions as the positive electrode active material is LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.33 Mn 0.33 Co 0.33 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co0.1 O2 and LiNi 0.90 Mn 0.05 Co 0.05 At least one selected from the group consisting of LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2 and LiNi 0.8 Mn 0.1 Co 0.1 More preferably, the compound is at least one selected from the group consisting of O2.

[0022] The lithium-nickel composite oxide represented by the general formula (1) may be used in combination with a different positive electrode active material. Specifically, LiCoO 2、 LiMnO2, LiMn2O4, Li2MnO 3、 LiMn 1.8 Al 0.2 O 4、 Li4Ti5O 12、 LiFePO4, Li3Fe2(PO4)3, LiFeP2O 7、 LiCoPO4, Li 1.2 Fe 0.4 Mn 0.4 O2, LiNiO2, etc.

[0023] Examples of lithium-containing transition metal oxides that function as negative electrode active materials include Li 4+x Ti5O 12 (0≦x≦3) and Li with ramsteride structure 2+y Examples of lithium titanates include Ti3O7 (0≦y≦3).

[0024] The lithium-containing transition metal oxide may be a lithium-containing transition metal oxide having a substance of a different composition attached to its surface. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.

[0025] These surface attachment substances can be attached to the surface of the lithium-containing transition metal oxide by, for example, a method in which the surface attachment substance precursor is dissolved or suspended in a solvent, added to the lithium-containing transition metal oxide by impregnation, and then dried; a method in which the surface attachment substance precursor is dissolved or suspended in a solvent, added to the lithium-containing transition metal oxide by impregnation, and then reacted by heating or the like; a method in which the surface attachment substance precursor is added to the lithium-containing transition metal oxide precursor and then calcined at the same time; or the like.

[0026] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, even more preferably 10 ppm or more, and preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less, by mass relative to the lithium-containing transition metal oxide. The surface-attached substance can suppress the oxidation reaction of the nonaqueous electrolyte on the surface of the lithium-containing transition metal oxide, and can improve the battery life, but if the amount of attachment is too small, the effect is not fully exerted, and if it is too large, the ingress and egress of lithium ions is inhibited, which may increase the resistance.

[0027] The shape of the lithium-containing transition metal oxide particles may be agglomerated, polyhedral, spherical, elliptical, plate-like, needle-like, columnar, etc., as has been conventionally used. Among them, primary particles are aggregated to form secondary particles, and the secondary particles are preferably spherical or elliptical. Normally, in an electrochemical element, the active material in the electrode expands and contracts with charging and discharging, and the active material is easily damaged by the stress, such as broken conductive paths. Therefore, a primary particle aggregated to form a secondary particle is preferable to a single particle active material consisting of only primary particles, because it relieves the stress of expansion and contraction and prevents deterioration. In addition, spherical or elliptical particles are preferable to plate-like equiaxially oriented particles, because they are less oriented when forming the electrode, so the electrode expands and contracts less when charging and discharging, and are easily mixed uniformly with a conductive assistant when preparing the electrode.

[0028] The tap density of lithium-containing transition metal oxides is typically 1.3 g / cm 3 More than 1.5 g / cm, preferably 1.5 g / cm 3 More preferably, 1.6 g / cm 3 More preferably, 1.7 g / cm 3 That is all. If the tap density of the lithium-containing transition metal oxide is below the lower limit, the amount of dispersion medium required during the formation of the electrode mixture layer increases, and the amount of conductive assistant and binder required also increases, which may restrict the filling rate of the lithium-containing transition metal oxide in the electrode mixture layer and restrict the battery capacity. By using a lithium-containing transition metal oxide with a high tap density, a high-density electrode mixture layer can be formed. Generally, the higher the tap density, the more preferable it is, and there is no particular upper limit. However, if the tap density is too high, the diffusion of lithium ions in the electrode mixture layer using the nonaqueous electrolyte as a medium becomes rate-limiting, and the load characteristics may be easily deteriorated. Therefore, the tap density is usually set to 2.5 g / cm. 3 Less than 2.4 g / cm 3 The following is the result.

[0029] The tap density of the lithium-containing transition metal oxide is measured by passing it through a sieve with an opening of 300 μm at 20 cm 3After dropping a sample into the tapping cell to fill the cell volume, tapping is performed 1,000 times with a stroke length of 10 mm using a powder density measuring device (for example, Tap Denser manufactured by Seishin Enterprise Co., Ltd.), and the density calculated from the volume and weight of the sample at that time is defined as the tap density.

[0030] The median diameter d50 of the lithium-containing transition metal oxide particles (secondary particle diameter when primary particles are aggregated to form secondary particles) is usually 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and most preferably 3 μm or more, and usually 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, and most preferably 15 μm or less. When the median diameter d50 of the lithium-containing transition metal oxide particles is within the above range, the electrode mixture of the present disclosure has excellent coating properties. Here, by using two or more types of lithium-containing transition metal oxides having different median diameters d50 in combination, the electrode mixture of the present disclosure can form a high-density electrode mixture layer.

[0031] In the present disclosure, the median diameter d50 is measured by a known laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used as the dispersion medium for the measurement, and the measurement is performed after ultrasonic dispersion for 5 minutes with a measurement refractive index set to 1.24.

[0032] When the primary particles are aggregated to form secondary particles, the average primary particle diameter of the lithium-containing transition metal oxide is usually 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, and most preferably 0.1 μm or more, and usually 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. Since the average primary particle diameter of the lithium-containing transition metal oxide is within the above range, spherical secondary particles are easily formed, the powder packing is excellent, and the crystallinity is also excellent, so that the electrode mixture of the present disclosure can form an electrode mixture layer with better flexibility and adhesion to the current collector, and a secondary battery with better battery characteristics can be formed. The primary particle diameter is measured by observation using a scanning electron microscope (SEM). Specifically, the longest value of the intercept of the left and right boundaries of the primary particles with respect to a horizontal line in a photograph at a magnification of 10,000 times is obtained for any 50 primary particles, and the average value is obtained.

[0033] The BET specific surface area of ​​lithium-containing transition metal oxides is typically 0.2 m 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 / g or more, typically 4.0m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 1.5m 2 When the BET specific surface area of ​​the lithium-containing transition metal oxide is within the above range, the electrode mixture of the present disclosure has excellent coatability, and can form an electrode mixture layer with improved flexibility and adhesion to a current collector, and can form a secondary battery with improved battery characteristics.

[0034] The BET specific surface area is defined as the value measured by a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.) by pre-drying a sample at 150°C for 30 minutes under a nitrogen flow, and then measuring the value by a nitrogen adsorption BET single-point method using a gas flow method, using a nitrogen-helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.

[0035] A method for producing lithium-containing transition metal oxide is generally used as a method for producing inorganic compounds. In particular, various methods are conceivable for producing a lithium-containing transition metal oxide in the form of a sphere or ellipsoid. For example, a method for dissolving or grinding and dispersing a transition metal raw material such as a transition metal nitrate or sulfate, and a raw material of other elements as necessary, in a solvent such as water, adjusting the pH while stirring to produce and recover a spherical precursor, drying this as necessary, adding a Li source such as LiOH, Li2CO3, or LiNO3, and firing at a high temperature to obtain a lithium-containing transition metal oxide; a method for dissolving or grinding a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, or oxide, and a raw material of other elements as necessary, in a solvent such as water; a method in which a transition metal source material such as a transition metal nitrate, sulfate, hydroxide or oxide, a Li source such as LiOH, Li2CO3 or LiNO3, and, if necessary, source materials of other elements are dissolved or pulverized and dispersed in a solvent such as water, and then dried and shaped using a spray dryer or the like to form a spherical or ellipsoidal precursor, which is then sintered at a high temperature to obtain a lithium-containing transition metal oxide.

[0036] The lithium-containing transition metal oxide may be used alone or in any combination and ratio of two or more kinds having different compositions or different powder properties.

[0037] The content of the lithium-containing transition metal oxide in the electrode mixture is preferably 95.0 to 99.8 mass%, more preferably 96.0 to 99.4 mass%, and even more preferably 96.5 to 99.0 mass%, relative to the total mass of the lithium-containing transition metal oxide, the conductive assistant, and the binder, because an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0038] <Conductive assistant> The conductive assistant contained in the electrode mixture of the present disclosure contains at least one nanocarbon material selected from the group consisting of multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes, and graphenes. Since the electrode mixture of the present disclosure contains a specific nanocarbon material as a conductive assistant, it is possible to obtain an electrode mixture layer having excellent adhesion to a current collector without impairing flexibility by forming an electrode mixture layer of an electrode of a secondary battery using the electrode mixture of the present disclosure. Furthermore, a secondary battery having such an electrode mixture layer exhibits a high high-temperature storage capacity retention rate, a low resistance increase rate, and a low gas amount change rate, and has excellent battery characteristics.

[0039] A nanocarbon material is a material formed of carbon atoms having a nanometer size. The shape of the nanocarbon material may be a cylinder, a hollow needle, a hollow rod, a hollow particle, or a sheet. In addition, the nanocarbon material is preferably conductive.

[0040] The nanocarbon material may be at least one selected from the group consisting of multi-walled carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerenes and graphenes, and is not particularly limited thereto, but since it is possible to form an electrode mixture layer with better flexibility and adhesion to the current collector, and to form a secondary battery with better battery characteristics, at least one selected from the group consisting of multi-walled carbon nanotubes, carbon nanohorns and graphenes is preferred, at least one selected from the group consisting of multi-walled carbon nanotubes and graphenes is more preferred, and multi-walled carbon nanotubes are even more preferred. The nanocarbon material may be used alone or in any combination and ratio of two or more types.

[0041] Graphene is a two-dimensional material, distinct from carbon nanotubes, which are known as one-dimensional materials. Carbon nanotubes are graphene sheets rolled into a cylindrical shape. Carbon nanotubes with a single wall are called single-walled carbon nanotubes (SWNTs) and those with multiple walls are called multi-walled carbon nanotubes (MWNTs).

[0042] The conductive assistant contained in the electrode mixture of the present disclosure preferably contains other conductive assistants other than the nanocarbon material. Examples of the conductive assistants other than the nanocarbon material include carbon black such as acetylene black and ketjen black, natural graphite, and metal powders such as nickel and aluminum.

[0043] As the conductive assistant other than the nanocarbon material, carbon black is preferable, and acetylene black is more preferable.

[0044] The content of the conductive assistant in the electrode mixture is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.3 mass% or more, particularly preferably 0.5 mass% or more, preferably 3.0 mass% or less, more preferably 2.5 mass% or less, even more preferably 2.0 mass% or less, and particularly preferably 1.6 mass% or less, relative to the total mass of the lithium-containing transition metal oxide, the conductive assistant, and the binder, because an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0045] The content of the nanocarbon material in the electrode mixture is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.2 mass% or more, still more preferably 0.3 mass% or more, particularly preferably 0.5 mass% or more, preferably 3.0 mass% or less, more preferably 2.5 mass% or less, still more preferably 2.0 mass% or less, and particularly preferably 1.6 mass% or less, relative to the total mass of the lithium-containing transition metal oxide, conductive assistant, and binder, since an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0046] When the electrode mixture of the present disclosure contains a nanocarbon material and another conductive assistant other than the nanocarbon material as a conductive assistant, the content ratio of the nanocarbon material and the other conductive assistant is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 95 / 5, and even more preferably 20 / 80 to 90 / 10 in mass ratio (mass of conductive assistant other than the nanocarbon material / mass of the nanocarbon material), since an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0047] <Binder> The binder contained in the electrode mixture of the present disclosure contains a fluorine-containing copolymer that contains vinylidene fluoride units (VdF units) and fluorinated monomer units (excluding VdF units).

[0048] Examples of the fluorinated monomer (excluding VdF) include tetrafluoroethylene (TFE), vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropene, and trans-1,3,3,3-tetrafluoropropene. Among them, at least one selected from the group consisting of TFE, CTFE, and HFP is preferred, at least one selected from the group consisting of TFE and HFP is more preferred, and TFE is particularly preferred, because it can form an electrode mixture layer with better flexibility and adhesion to the current collector, and can form a secondary battery with better battery characteristics.

[0049] The fluorinated monomer units (except for the VdF units) may or may not have a polar group.

[0050] The content of VdF units in the fluorine-containing copolymer is more than 50 mol % and not more than 99 mol % based on the total monomer units. When the content of VdF units is within the above range, an electrode mixture layer excellent in flexibility and adhesion to the current collector can be formed, and a secondary battery excellent in battery characteristics can be formed. If the content of VdF units in the fluorine-containing copolymer is too low, sufficient adhesion of the electrode mixture layer to the current collector cannot be obtained, and excellent battery characteristics of the secondary battery cannot be obtained.

[0051] The content of VdF units in the fluorine-containing copolymer is preferably 57.0 mol % or more, more preferably 60.0 mol % or more, even more preferably 63.0 mol % or more, preferably 99.0 mol % or less, more preferably 97.0 mol % or less, even more preferably 95.0 mol % or less, particularly preferably 90.0 mol % or less, and most preferably 85.0 mol % or less, relative to all monomer units, since an electrode mixture layer with better flexibility and adhesion to a current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0052] The content of the fluorinated monomer unit (excluding VdF unit) of the fluorine-containing copolymer is not particularly limited as long as it is less than 50 mol%, but is preferably 1.0 mol% or more, more preferably 3.0 mol% or more, even more preferably 5.0 mol% or more, particularly preferably 10.0 mol% or more, most preferably 15.0 mol% or more, preferably 43.0 mol% or less, more preferably 40.0 mol% or less, and even more preferably 37.0 mol% or less, based on the total monomer units. By containing a fluorine-containing copolymer having a content of the fluorinated monomer unit (excluding VdF unit) in the above range, the electrode mixture of the present disclosure can form an electrode mixture layer with better flexibility and adhesion to the current collector, and can form a secondary battery with better battery characteristics.

[0053] In the present disclosure, the composition of the fluorine-containing copolymer is, for example, 19 It can be measured by F-NMR measurement.

[0054] The fluorine-containing copolymer may further contain a non-fluorinated monomer unit. Examples of the non-fluorinated monomer include a non-fluorinated monomer having no polar group, such as ethylene or propylene, and a non-fluorinated monomer having a polar group (hereinafter sometimes referred to as a polar group-containing monomer).

[0055] When a non-fluorinated monomer having a polar group is used, the polar group is introduced into the fluorine-containing copolymer, which provides even better adhesion between the positive electrode mixture layer and the current collector. The polar group that the fluorine-containing copolymer may have is preferably at least one selected from the group consisting of a carbonyl group-containing group, an epoxy group, a hydroxy group, a sulfonic acid group, a sulfate group, a phosphoric acid group, an amino group, an amide group, and an alkoxy group, more preferably at least one selected from the group consisting of a carbonyl group-containing group, an epoxy group, and a hydroxy group, and even more preferably a carbonyl group-containing group. The hydroxy group does not include a hydroxy group that constitutes a part of the carbonyl group-containing group. The amino group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary amine, or a secondary amine.

[0056] The carbonyl-containing group is a functional group having a carbonyl group (-C(=O)-). The carbonyl-containing group is preferably a group represented by the general formula -COOR (R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group) or a carboxylic anhydride group. The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3. Specific examples of the group represented by the general formula -COOR include -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, and -COOC2H5. When the group represented by the general formula -COOR is -COOH or contains -COOH, -COOH may be a carboxylate such as a metal carboxylate or an ammonium carboxylate.

[0057] The carbonyl group-containing group may be a group represented by the general formula: -X-COOR (X is composed of 2 to 15 atoms, and the molecular weight of the atomic group represented by X is preferably 350 or less, and R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and further preferably 1 to 3.

[0058] The amide group is preferably a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group), or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted phenyl group).

[0059] Examples of the polar group-containing monomer include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; alkylidene malonic acid esters such as dimethyl methylidene malonate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylate esters such as acryloyloxyethyl succinate, acryloyloxypropyl succinate, methacryloyloxyethyl succinate, acryloyloxyethyl phthalate, and methacryloyloxyethyl phthalate; monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; [ka] (In the formula, R 1 ~R 3 R independently represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. 4 represents a single bond or a hydrocarbon group having 1 to 8 carbon atoms. 1 represents an inorganic cation and / or an organic cation.

[0060] The polar group-containing monomer unit which the fluorine-containing copolymer may contain is preferably a unit based on the monomer (2) represented by the general formula (2).

[0061] In the general formula (2), Y1 represents an inorganic cation and / or an organic cation. Examples of inorganic cations include cations such as H, Li, Na, K, Mg, Ca, Al, and Fe. Examples of organic cations include NH4, NH3R 5 , NH2R 5 2. NHR 5 3. NR 5 4(R 5 Each of Y independently represents an alkyl group having 1 to 4 carbon atoms. 1 As the cation, H, Li, Na, K, Mg, Ca, Al, and NH4 are preferable, H, Li, Na, K, Mg, Al, and NH4 are more preferable, H, Li, Al, and NH4 are further preferable, and H is particularly preferable. For the sake of convenience, the symbols and valences of the specific examples of the inorganic cations and the organic cations are omitted.

[0062] In the general formula (2), R 1 ~R 3 R independently represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. The above hydrocarbon group is a monovalent hydrocarbon group. The above hydrocarbon group preferably has 4 or less carbon atoms. Examples of the above hydrocarbon group include alkyl groups, alkenyl groups, alkynyl groups, etc. having the above carbon numbers, and a methyl group or an ethyl group is preferred. 1 and R 2 are preferably independently a hydrogen atom, a methyl group or an ethyl group, and R 3 is preferably a hydrogen atom or a methyl group.

[0063] In the general formula (2), R 4 represents a single bond or a hydrocarbon group having 1 to 8 carbon atoms. The above hydrocarbon group is a divalent hydrocarbon group. The above hydrocarbon group preferably has 4 or less carbon atoms. Examples of the above hydrocarbon group include alkylene groups and alkenylene groups having the above carbon numbers, and among these, at least one selected from the group consisting of a methylene group, an ethylene group, an ethylidene group, a propylidene group and an isopropylidene group is preferable, and a methylene group is more preferable.

[0064] The monomer (2) is preferably at least one selected from the group consisting of (meth)acrylic acid and its salts, vinylacetic acid (3-butenoic acid) and its salts, 3-pentenoic acid and its salts, 4-pentenoic acid and its salts, 3-hexenoic acid and its salts, 4-heptenoic acid and its salts, and 5-hexenoic acid and its salts, and more preferably at least one selected from the group consisting of 3-butenoic acid and its salts, and 4-pentenoic acid and its salts.

[0065] When the fluorine-containing copolymer contains the above-mentioned polar group-containing monomer unit, the content of the above-mentioned polar group-containing monomer unit in the fluorine-containing copolymer is preferably 0.05 to 2.0 mol %, more preferably 0.10 mol % or more, even more preferably 0.25 mol % or more, particularly preferably 0.40 mol % or more, and more preferably 1.5 mol % or less, based on the total monomer units.

[0066] In the present disclosure, the content of the polar group-containing monomer unit in the fluorine-containing copolymer can be measured, for example, when the polar group is an acid group such as carboxylic acid, by acid-base titration of the acid group.

[0067] Examples of the fluorine-containing copolymer include VdF / TFE copolymer, VdF / HFP copolymer, VdF / TFE / HFP copolymer, VdF / TFE / 2,3,3,3-tetrafluoropropene copolymer, VdF / TFE / (meth)acrylic acid copolymer, VdF / HFP / (meth)acrylic acid copolymer, VdF / CTFE copolymer, VdF / TFE / 4-pentenoic acid copolymer, VdF / TFE / 3-butenoic acid copolymer, VdF / TFE / H Examples of such copolymers include FP / (meth)acrylic acid copolymer, VdF / TFE / HFP / 4-pentenoic acid copolymer, VdF / TFE / HFP / 3-butenoic acid copolymer, VdF / TFE / 2-carboxyethyl acrylate copolymer, VdF / TFE / HFP / 2-carboxyethyl acrylate copolymer, VdF / TFE / acryloyloxyethyl succinic acid copolymer, and VdF / TFE / HFP / acryloyloxyethyl succinic acid copolymer.

[0068] As the fluorine-containing copolymer, a fluorine-containing copolymer consisting only of VdF units, TFE units and any non-fluorinated monomer units is preferred, since it can form an electrode mixture layer having better flexibility and adhesion to a current collector, and can form a secondary battery having better battery characteristics.

[0069] When the fluorine-containing copolymer contains VdF units and TFE units, the molar ratio of VdF units to TFE units (VdF units / TFE units) is preferably more than 50 / 50 and not more than 99 / 1, more preferably from 57 / 43 to 97 / 3, still more preferably from 60 / 40 to 95 / 5, particularly preferably from 63 / 37 to 90 / 10, and most preferably from 63 / 37 to 85 / 15.

[0070] The weight average molecular weight (polystyrene equivalent) of the fluorine-containing copolymer is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, particularly preferably 200,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0071] The number average molecular weight (polystyrene equivalent) of the fluorine-containing copolymer is preferably 20,000 to 1,500,000, more preferably 40,000 or more, even more preferably 70,000 or more, particularly preferably 140,000 or more, more preferably 1,400,000 or less, even more preferably 1,200,000 or less, and particularly preferably 1,100,000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0072] The melting point of the fluorocopolymer is preferably 100 to 170° C., more preferably 110 to 165° C., and further preferably 120 to 163° C. The melting point is determined as the temperature corresponding to the maximum value on the heat of fusion curve obtained by using a differential scanning calorimetry (DSC) device, heating from 30° C. to 220° C. at a rate of 10° C. / min, then lowering to 30° C. at 10° C. / min, and again heating to 220° C. at a rate of 10° C. / min.

[0073] The fluorocopolymer preferably has an elongation at break of 100% or more, more preferably 200% or more, and even more preferably 300% or more.

[0074] The elongation at break can be measured by the following method. A fluorocopolymer solution obtained by dissolving a fluorocopolymer in N-methyl-2-pyrrolidone (NMP) to a concentration of 10 to 20% by mass is cast onto a glass plate and dried at 100°C for 12 hours, and further dried under vacuum at 100°C for 12 hours to obtain a film having a thickness of 50 to 100 μm. The film is punched into a dumbbell shape, and the elongation at break at 25°C is measured using an autograph.

[0075] The fluorocopolymer preferably has a storage modulus at 30°C of 1100 MPa or less and a storage modulus at 60°C of 500 MPa or less. The storage modulus of the fluorocopolymer at 30° C. is more preferably 800 MPa or less, and further preferably 600 MPa or less. The storage modulus of the fluorocopolymer at 60° C. is more preferably 350 MPa or less. The storage modulus of the fluorocopolymer at 30° C. is preferably 100 MPa or more, more preferably 150 MPa or more, and further preferably 200 MPa or more. The storage modulus of the fluorocopolymer at 60° C. is preferably 50 MPa or more, more preferably 80 MPa or more, and further preferably 130 MPa or more.

[0076] The storage modulus is the measured value at 30°C and 60°C for a sample with a length of 30 mm, width of 5 mm, and thickness of 50 to 100 μm, measured using a dynamic viscoelasticity measurement device DVA220 manufactured by IT Measurement & Control Co., Ltd. under the following conditions: tensile mode, gripping width of 20 mm, measurement temperature from -30°C to 160°C, heating rate of 2°C / min, and frequency of 1 Hz.

[0077] A measurement sample can be prepared, for example, by dissolving a fluorine-containing copolymer in N-methyl-2-pyrrolidone (NMP) to a concentration of 10 to 20 mass%, casting the resulting fluorine-containing copolymer solution onto a glass plate, drying at 100°C for 12 hours, and further drying under vacuum at 100°C for 12 hours, and cutting the resulting film having a thickness of 50 to 100 μm into a length of 30 mm and a width of 5 mm.

[0078] The fluorocopolymer preferably has a weight increase rate of 250% by mass or less, more preferably 200% by mass or less, after immersion in an electrolytic solution at 60° C. for one week. The weight increase rate of the fluorocopolymer after immersion in an electrolytic solution at 60° C. for one week is further preferably 180% by mass or less, particularly preferably 160% by mass or less, and may be 105% by mass or more.

[0079] The weight increase rate can be determined by the following method. A 200 μm thick film of the fluorocopolymer is produced by casting an NMP solution (8% by mass) on a glass petri dish and vacuum drying for 12 hours at 100° C. The obtained film is punched out to a size of 6 mm Φ and placed in a sample bottle containing an electrolyte (a solution of LiPF6 dissolved at a concentration of 1 M in a solvent of ethylene carbonate / ethyl methyl carbonate at a volume ratio of 3 / 7), and left to stand at 60° C. for one week, after which the weight increase rate is determined.

[0080] The binder contained in the electrode mixture of the present disclosure preferably further contains polyvinylidene fluoride (PVdF). By using a fluorine-containing copolymer and PVdF as the binder, an electrode mixture layer having better flexibility and adhesion to the current collector can be formed, and a secondary battery having better battery characteristics can be formed.

[0081] Polyvinylidene fluoride (PVdF) is a polymer containing units based on vinylidene fluoride (VdF) (hereinafter referred to as VdF units), and may be a VdF homopolymer consisting of only VdF units, or a polymer containing VdF units and units based on a monomer copolymerizable with VdF.

[0082] In the above PVdF, the monomer copolymerizable with VdF is preferably a monomer other than tetrafluoroethylene (TFE), that is, PVdF preferably does not contain a TFE unit.

[0083] In the above PVdF, examples of the monomer copolymerizable with VdF include fluorinated monomers and non-fluorinated monomers, and fluorinated monomers are preferred. Examples of the above fluorinated monomers include vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), fluoroalkyl vinyl ether, hexafluoropropylene (HFP), (perfluoroalkyl)ethylene, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, and the like. Examples of the above non-fluorinated monomers include ethylene and propylene.

[0084] In the above-mentioned PVdF, the monomer copolymerizable with VdF is preferably at least one fluorinated monomer selected from the group consisting of CTFE, fluoroalkyl vinyl ether, HFP, and 2,3,3,3-tetrafluoropropene, and more preferably at least one fluorinated monomer selected from the group consisting of CTFE, HFP, and fluoroalkyl vinyl ether.

[0085] In the above PVdF, the content of the monomer units copolymerizable with VdF is preferably 0 to 5.0 mol%, more preferably 0 to 3.0 mol%, based on the total monomer units. In the above PVdF, the content of the fluorinated monomer units copolymerizable with VdF is preferably less than 5.0 mol%, more preferably less than 3.0 mol%, and even more preferably less than 1.0 mol%, based on the total monomer units.

[0086] In the present disclosure, the composition of PVdF is, for example, 19 It can be measured by F-NMR measurement.

[0087] The PVdF may have a polar group. By using a fluorine-containing copolymer and PVdF having a polar group as a binder, an electrode mixture layer having better flexibility and adhesion to a current collector can be formed, and a secondary battery having better battery characteristics can be formed.

[0088] The polar group is not particularly limited as long as it is a functional group having polarity, but since it is possible to further improve the adhesion of the electrode mixture layer to the current collector while maintaining the excellent flexibility of the electrode mixture layer formed and the excellent battery characteristics of the secondary battery formed, at least one selected from the group consisting of a carbonyl group-containing group, an epoxy group, a hydroxy group, a sulfonic acid group, a sulfate group, a phosphoric acid group, an amino group, an amide group, and an alkoxy group is preferable, at least one selected from the group consisting of a carbonyl group-containing group, an epoxy group, and a hydroxy group is more preferable, and a carbonyl group-containing group is even more preferable. The hydroxy group does not include a hydroxy group that constitutes a part of the carbonyl group-containing group. The amino group is a monovalent functional group obtained by removing hydrogen from ammonia, a primary amine, or a secondary amine.

[0089] The carbonyl group-containing group is a functional group having a carbonyl group (-C(=O)-). As the carbonyl group-containing group, a group represented by the general formula -COOR (R represents a hydrogen atom, an alkyl group or a hydroxyalkyl group) or a carboxylic anhydride group is preferred, and a group represented by the general formula -COOR is more preferred, because it can further improve the adhesion of the electrode mixture layer to the current collector while maintaining the excellent flexibility of the electrode mixture layer formed and the excellent battery characteristics of the secondary battery formed. The number of carbon atoms of the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and even more preferably 1 to 3. Specific examples of the group represented by the general formula -COOR include -COOCH2CH2OH, -COOCH2CH(CH3)OH, -COOCH(CH3)CH2OH, -COOH, -COOCH3, and -COOC2H5. When the group represented by the general formula: -COOR is -COOH or contains -COOH, the -COOH may be a carboxylate such as a metal carboxylate or an ammonium carboxylate.

[0090] The carbonyl group-containing group may be a group represented by the general formula: -X-COOR (X is composed of 2 to 15 atoms, and the molecular weight of the atomic group represented by X is preferably 350 or less, and R represents a hydrogen atom, an alkyl group, or a hydroxyalkyl group). The number of carbon atoms in the alkyl group and the hydroxyalkyl group is preferably 1 to 16, more preferably 1 to 6, and further preferably 1 to 3.

[0091] The amide group is preferably a group represented by the general formula: -CO-NRR' (R and R' independently represent a hydrogen atom or a substituted or unsubstituted alkyl group), or a bond represented by the general formula: -CO-NR"- (R" represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted phenyl group).

[0092] The polar group can be introduced into PVdF by polymerizing VdF with a monomer having the polar group (hereinafter referred to as a polar group-containing monomer), or by reacting PVdF with a compound having the polar group. From the viewpoint of productivity, however, it is preferable to polymerize VdF with the polar group-containing monomer.

[0093] Polymerization of VdF and the polar group-containing monomer produces PVdF containing VdF units and polar group-containing monomer units. That is, PVdF preferably contains the polar group-containing monomer units because it can improve the adhesion of the electrode mixture layer to the current collector while maintaining the excellent flexibility of the electrode mixture layer and the excellent battery characteristics of the secondary battery. The content of the polar group-containing monomer units is preferably 0.001 to 5.0 mol%, more preferably 0.01 to 3.0 mol%, and even more preferably 0.10 to 1.5 mol% based on the total monomer units.

[0094] In the present disclosure, the content of polar group-containing monomer units in PVdF can be measured, for example, by acid-base titration of the acid group when the polar group is an acid group such as a carboxylic acid.

[0095] Examples of the polar group-containing monomer include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinyl acetic acid (3-butenoic acid), 3-pentenoic acid, 4-pentenoic acid, 3-hexenoic acid, and 4-heptenoic acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonic acid esters such as dimethyl methylidene malonate; vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether; Examples of the carboxyalkyl (meth)acrylates include 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, and other carboxyalkyl (meth)acrylates; (meth)acryloyloxyalkyl dicarboxylates such as acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxyethyl phthalate, acryloyloxypropyl succinate, and methacryloyloxyethyl phthalate; and monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester.

[0096] When the polar group is introduced into PVdF by reacting PVdF with the compound having the polar group, the polar group-containing monomer, or a silane coupling agent or titanate coupling agent having a group reactive with PVdF and a hydrolyzable group can be used as the compound having the polar group. The hydrolyzable group is preferably an alkoxy group. When a coupling agent is used, it can be added to PVdF by reacting with PVdF dissolved or swollen in a solvent.

[0097] Alternatively, PVdF may be obtained by partially dehydrofluorinating PVdF with a base, and then reacting the partially dehydrofluorinated PVdF with an oxidizing agent, such as hydrogen peroxide, hypochlorite, palladium halide, chromium halide, alkali metal permanganate, peracid compound, alkyl peroxide, or alkyl persulfate.

[0098] The content of VdF units in PVdF is preferably more than 95.0 mol%, more preferably more than 97.0 mol%, and even more preferably more than 99.0 mol%, based on the total monomer units, because this allows the formation of an electrode mixture layer with better flexibility and adhesion to a current collector, and allows the formation of a secondary battery with better battery characteristics. Furthermore, the content of VdF units in PVdF is preferably 95.0 to 99.999 mol %, more preferably 97.0 mol % or more, even more preferably 98.5 mol % or more, more preferably 99.99 mol % or less, and even more preferably 99.90 mol % or less, relative to all monomer units, because this allows the formation of an electrode mixture layer with even better flexibility and adhesion to a current collector, and allows the formation of a secondary battery with even better battery characteristics.

[0099] The weight average molecular weight (polystyrene equivalent) of PVdF is preferably 50000 to 3000000, more preferably 80000 or more, even more preferably 100000 or more, particularly preferably 200000 or more, more preferably 2400000 or less, even more preferably 2200000 or less, and particularly preferably 2000000 or less, because an electrode mixture layer having excellent flexibility and adhesion to a current collector can be formed, and a secondary battery having excellent battery characteristics can be formed. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using N,N-dimethylformamide as a solvent. In addition, since an electrode mixture layer having excellent flexibility and adhesion to a current collector can be formed, and a secondary battery having excellent battery characteristics can be formed, the weight average molecular weight of PVdF (A) may be 1000000 or more, or may be 1500000 or more.

[0100] The number average molecular weight (polystyrene equivalent) of PVdF is preferably 20000 to 1500000, more preferably 40000 or more, even more preferably 70000 or more, particularly preferably 140000 or more, more preferably 1400000 or less, even more preferably 1200000 or less, and particularly preferably 1100000 or less, since an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0101] The melting point of PVdF is preferably 100 to 240° C. The melting point can be determined as the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimetry (DSC) device.

[0102] PVdF can be produced by a conventional method such as, for example, mixing VdF, the polar group-containing monomer, and additives such as a polymerization initiator in an appropriate amount, and carrying out solution polymerization or suspension polymerization.

[0103] The storage modulus of PVdF at 30° C. is preferably 2000 MPa or less, and more preferably 1800 MPa or less. The storage modulus of PVdF at 60° C. is preferably 1500 MPa or less, and more preferably 1300 MPa or less. The storage modulus of PVdF at 30° C. is preferably 1000 MPa or more, and more preferably 1100 MPa or more. The storage modulus of PVdF at 60° C. is preferably 600 MPa or more, and more preferably 700 MPa or more. The storage modulus of PVdF can be measured by the same method as that for the storage modulus of a fluorocopolymer.

[0104] When the binder contains PVdF in addition to the fluorine-containing copolymer, the mass ratio of PVdF to the fluorine-containing copolymer in the binder (PVdF / fluorine-containing copolymer) is preferably 99 / 1 to 1 / 99, more preferably 97 / 3 to 3 / 97, still more preferably 95 / 5 to 5 / 95, particularly preferably 90 / 10 to 10 / 90, particularly preferably 85 / 15 to 15 / 85, and most preferably 80 / 20 to 40 / 60, since an electrode mixture layer with even better flexibility and adhesion to the current collector can be formed, and a secondary battery with even better battery characteristics can be formed.

[0105] The binder may contain other polymers in addition to PVdF and the fluorine-containing copolymer, such as polymethacrylate, polymethyl methacrylate, polyacrylonitrile, polyimide, polyamide, polyamideimide, polycarbonate, styrene rubber, butadiene rubber, etc.

[0106] The content of the fluorine-containing copolymer in the binder is preferably 1 mass % or more, more preferably 3 mass % or more, even more preferably 5 mass % or more, particularly preferably 10 mass % or more, and most preferably 15 mass % or more, and may be 100 mass % or less, relative to the mass of the binder, because an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0107] The content of the binder in the electrode mixture is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, even more preferably 0.3 mass % or more, particularly preferably 0.5 mass % or more, preferably 3.0 mass % or less, more preferably 2.5 mass % or less, and even more preferably 2.0 mass % or less, relative to the total mass of the lithium-containing transition metal oxide, the conductive assistant, and the binder, because an electrode mixture layer with better flexibility and adhesion to the current collector can be formed, and a secondary battery with better battery characteristics can be formed.

[0108] <Organic solvent> The electrode mixture of the present disclosure further contains an organic solvent. Examples of the organic solvent include nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone-based solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester-based solvents such as ethyl acetate and butyl acetate; ether-based solvents such as tetrahydrofuran and dioxane; β-alkoxypropionamides such as β-methoxy-N,N-dimethylpropionamide, β-n-butoxy-N,N-dimethylpropionamide, and β-n-hexyloxy-N,N-dimethylpropionamide; and low-boiling general-purpose organic solvents such as their mixed solvents. Among these, the solvent is preferably at least one selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and β-alkoxypropionamides, from the viewpoint of excellent coating properties, and more preferably at least one selected from the group consisting of N-methyl-2-pyrrolidone and N,N-dimethylacetamide.

[0109] The contents of the lithium-containing transition metal oxide, binder, and carbon nanomaterial in the electrode mixture of the present disclosure are determined in consideration of the coatability onto the current collector, thin film formability after drying, etc. The total content of the lithium-containing transition metal oxide, binder, and carbon nanomaterial in the electrode mixture is preferably 50 to 90 mass%, more preferably 60 to 80 mass%.

[0110] The electrode mixture of the present disclosure can be prepared by mixing a lithium-containing transition metal oxide, a binder, a nanocarbon material, an organic solvent, and other components as necessary. In this case, the order of mixing the components is not particularly limited. For example, the binder, the nanocarbon material, and the organic solvent may be mixed, and then the lithium-containing transition metal oxide and other components may be mixed. In addition, for example, a composite material of the binder and the lithium-containing transition metal oxide may be obtained by a method such as spraying a solution or dispersion of the binder onto the lithium-containing transition metal oxide and drying, and then the obtained composite material, the nanocarbon material, the organic solvent, and other components may be mixed.

[0111] In order to enable rapid dissolution in an organic solvent, it is desirable for the binder to be used with a small particle size of an average particle size of 1000 μm or less, particularly 50 to 350 μm.

[0112] <Electrode> The electrode of the present disclosure includes a current collector and an electrode mixture layer. The electrode mixture layer is formed using the electrode mixture of the present disclosure and may be provided on one side or both sides of the current collector.

[0113] The electrode of the present disclosure includes an electrode mixture layer formed using the electrode mixture of the present disclosure, and therefore has excellent flexibility, sufficient adhesion between the current collector and the electrode mixture layer, and is capable of forming a secondary battery with excellent battery characteristics.

[0114] The density of the electrode mixture layer is preferably 2.0 to 5.0 g / cm 3 and more preferably 2.5 to 5.0 g / cm 3It is.

[0115] The density of the electrode mixture layer can be calculated from the mass and volume of the electrode mixture layer.

[0116] The thickness of the electrode mixture layer is preferably 20 μm or more, more preferably 45 μm or more, even more preferably 55 μm or more, particularly preferably 60 μm or more, and preferably 170 μm or less, more preferably 150 μm or less, since even higher battery characteristics can be obtained. The thickness of the electrode mixture layer may be 85 μm or less, or may be less than 69 μm.

[0117] The thickness of the electrode mixture layer can be measured with a micrometer. In the present disclosure, the thickness of the electrode mixture layer is the thickness per one side when the electrode mixture layer is provided on both sides of the current collector.

[0118] Examples of the current collector provided in the electrode of the present disclosure include metal foils or metal meshes of iron, stainless steel, copper, aluminum, nickel, titanium, etc., and among these, aluminum foil is preferred.

[0119] The electrode of the present disclosure can be suitably manufactured by a manufacturing method in which the electrode mixture of the present disclosure is applied to a current collector. After the electrode mixture is applied, the coating may be further dried, and the resulting dried coating may be pressed.

[0120] The amount of the electrode mixture applied to the current collector is preferably 15 mg / cm. 2 More preferably, it is 17.5 mg / cm or more. 2 or more, preferably 60 mg / cm 2 More preferably, it is 50 mg / cm or less. 2 The coating amount of the electrode mixture is the dry weight of the electrode mixture per unit area.

[0121] <Secondary battery> The present disclosure also provides a secondary battery including the above electrode.

[0122] The secondary battery of the present disclosure includes an electrode formed using the electrode mixture of the present disclosure, and therefore exhibits a high high-temperature storage capacity retention rate, a low resistance increase rate, and a low gas amount change rate, and thus has excellent battery characteristics.

[0123] The secondary battery of the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte, and preferably one or both of the positive electrode and the negative electrode are the above-mentioned electrodes. Also, the secondary battery of the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte, and preferably the positive electrode is the above-mentioned electrode.

[0124] The non-aqueous electrolyte is not particularly limited, and one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyl lactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. Any of the conventionally known electrolytes can be used, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.

[0125] The electrode of the present disclosure has excellent flexibility, has sufficient adhesion between the current collector and the electrode mixture layer, and can form a secondary battery with excellent battery characteristics, and therefore can be suitably used as an electrode for a wound type secondary battery. In addition, the secondary battery of the present disclosure may be a wound type secondary battery.

[0126] The electrode of the present disclosure is useful for non-aqueous electrolyte secondary batteries, not only for lithium ion secondary batteries using the liquid electrolyte described above, but also for polymer electrolyte lithium secondary batteries, and is also useful for electric double layer capacitors.

[0127] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0128] Next, embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to such examples.

[0129] Each numerical value in the examples was measured by the following method.

[0130] <Content of acrylic acid units in PVdF> The content of acrylic acid units in PVdF was measured by acid-base titration of carboxylic acid groups. Specifically, about 0.5 g of PVdF was dissolved in acetone at a temperature of 70 to 80°C. 5 ml of water was added dropwise under vigorous stirring so as to avoid solidification of PVdF. Titration with an aqueous NaOH solution having a concentration of 0.1 N was carried out until complete neutralization of the acidity at a neutral transition at about -270 mV. From the measurement results, the content of the acrylic acid unit contained in 1 g of PVdF was determined, and the content of the acrylic acid unit was calculated.

[0131] <Ratio of VdF units and TFE units in the fluorine-containing copolymer> The ratio of VdF units and TFE units in the fluorine-containing copolymer was measured in a DMF-d7 solution state of the polymer by F-NMR measurement using an NMR analyzer (manufactured by Agilent Technologies, VNS400 MHz). 19

[0132] 19 By F-NMR measurement, the areas (A, B, C, D) of the following peaks were determined, and the ratio of VdF units and TFE units was calculated. A: Area of the peak at -86 ppm to -98 ppm B: Area of the peak at -105 ppm to -118 ppm C: Area of the peak at -119 ppm to -122 ppm D: Area of the peak at -122 ppm to -126 ppm Ratio of VdF units: (4A + 2B) / (4A + 3B + 2C + 2D) × 100 [mol%] Ratio of TFE units: (B + 2C + 2D) / (4A + 3B + 2C + 2D) × 100 [mol%]

[0133] ​<Weight average molecular weight> Measurements were performed by gel permeation chromatography (GPC). Calculations were performed using data measured with Tosoh AS-8010, CO-8020, columns (three GMHHR-H connected in series), and Shimadzu RID-10A, using dimethylformamide (DMF) as the solvent at a flow rate of 1.0 ml / min (reference: polystyrene).

[0134] <Melting point> Using a differential scanning calorimetry (DSC) device, the temperature was raised from 30°C to 220°C at a rate of 10°C / min, then lowered to 30°C at 10°C / min, and then raised again to 220°C at a rate of 10°C / min. The temperature corresponding to the maximum value on the heat of fusion curve was determined as the melting point.

[0135] <Thickness of positive electrode mixture layer> Test pieces were prepared by punching out the positive electrodes prepared in the examples and comparative examples with a hand punch of Φ13 mm, and the total thickness of the test pieces was measured with a micrometer with a minimum scale of 1 μm. The thickness was calculated by subtracting the thickness of the positive electrode current collector from these measured values.

[0136] <Density of Positive Electrode Mixture Layer> The positive electrodes prepared in the examples and comparative examples were punched out with a hand punch of Φ13 mm to prepare test pieces, and the mass and area of ​​the test pieces were measured. The density of the positive electrode mixture layer was calculated from the mass of the test piece and the positive electrode current collector, the area of ​​the test piece, and the thickness of the positive electrode mixture layer obtained by the above method.

[0137] <Adhesion between positive electrode mixture layer and current collector> A test piece of 1.2 cm x 7.0 cm was prepared by cutting the positive electrode prepared in the examples and comparative examples. The positive electrode mixture layer side of the test piece was fixed to a movable jig with double-sided tape, and then the tape was applied to the surface of the positive electrode current collector, and the stress (N / cm) when the tape was pulled at 90 degrees at a speed of 100 mm / min was measured by an autograph. A 1N load cell was used for the autograph.

[0138] <Positive electrode flexibility> The positive electrode mixture obtained in the examples and comparative examples was uniformly applied to one side of a positive electrode current collector (aluminum foil with a thickness of 20 μm), and the NMP was completely volatilized to prepare a positive electrode before pressing. A test piece of 2 cm × 10 cm was prepared by cutting the prepared positive electrode before pressing. The test piece was pressed to prepare a density-adjusted test piece in which the density of the positive electrode mixture layer was 3.6 g / cc. The density-adjusted test piece was wrapped around a round bar with a diameter of 5 mm and 3 mm, and the positive electrode mixture layer was visually confirmed and evaluated according to the following criteria. A: No cracks were observed. Δ: Cracking was observed, but no breakage was observed in the positive electrode mixture layer or the positive electrode current collector. ×: The positive electrode mixture layer and the positive electrode current collector were broken.

[0139] In the examples and comparative examples, polymers having the following physical properties were used. <pvdf> A: VdF homopolymer Weight average molecular weight 900000 Melting point: 171°C B: VdF homopolymer Weight average molecular weight 1800000 Melting point: 171°C C: PVdF containing acrylic acid units Acrylic acid unit content: 1.0 mol% Weight average molecular weight 1100000 Melting point: 161°C

[0140] <Fluorine-containing copolymer> a: Fluorine-containing copolymer containing VdF units and TFE units VdF / TFE=83 / 17 (mol%) Weight average molecular weight 1230000 Melting point: 131°C b: Fluorine-containing copolymer containing VdF units and TFE units VdF / TFE=63 / 37 (mol%) Weight average molecular weight 1130000 Melting point: 160℃ c: Fluorine-containing copolymer containing VdF units and TFE units VdF / TFE=50 / 50 (mol%)

[0141] In the examples and comparative examples, the following positive electrode active materials and conductive assistants were used. NMC622:LiNi 0.6 Mn 0.2 Co 0.2 O2 NMC811:LiNi 0.8 Mn 0.1 Co 0.1 O2 NCA:LiNi 0.82 Co 0.15 Al 0.03 O2 AB: Acetylene black CNT: Multi-walled carbon nanotubes, manufactured by C-Nano Co., Ltd., product name LB136-43 Graphene: Manufactured by Sanjun Chukasha, product name GNP-N

[0142] <Example 1> (Preparation of Positive Electrode Mixture) The fluorine-containing copolymer (a) as a binder was dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a fluorine-containing copolymer (a) solution with a concentration of 8% by mass. The fluorine-containing copolymer (a) solution, NMC622 as a positive electrode active material, acetylene black (AB) as a conductive assistant, and multi-walled carbon nanotubes (CNT) were mixed using a stirrer to obtain a mixed solution having the composition ratio (active material / conductive assistant / binder) shown in Table 1. NMP was further added to the obtained mixed solution and mixed to prepare a positive electrode mixture with a solid content concentration of 71% by mass.

[0143] (Preparation of positive electrode) The obtained positive electrode mixture was evenly applied to one side of a positive electrode current collector (aluminum foil having a thickness of 20 μm). After the NMP was completely evaporated, the resultant was pressed using a roll press machine at a pressure of 10 tons to produce a positive electrode including a positive electrode mixture layer and a positive electrode current collector. Table 1 shows the amount of positive electrode mixture applied per side, the thickness of the positive electrode mixture layer per side in the positive electrode, the density of the positive electrode mixture layer, and the adhesion of the positive electrode mixture layer to the positive electrode current collector.

[0144] (Preparation of NMC622 laminated cell) The prepared positive electrode was cut to 500mm x 700mm (with positive electrode terminal), and the strip-shaped negative electrode was cut to 502mm x 702mm (with negative electrode terminal), and a lead body was welded to each terminal. In addition, a 20μm thick polypropylene film separator was cut to a size of 504mm x 800mm, and the positive electrode and negative electrode were wound so as to sandwich the separator and placed in a packaging material. Next, 5g of electrolyte (LiPF6 dissolved at a concentration of 1 mol / liter in a solvent mixed with ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3 / 7) was placed in the packaging material and sealed to prepare a wound laminate battery.

[0145] <Evaluation of battery characteristics> The high-temperature storage capacity retention rate, resistance increase rate, and gas amount change rate of the wound laminate battery produced in Example 1 were measured by the following methods. The results are shown in Table 1.

[0146] [Initial Characterization] The wound laminate battery was sandwiched between plates and pressed, and then charged to 4.2V at 25°C with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was repeated for two cycles to stabilize the battery, and in the third cycle, the battery was charged to 4.2V with a constant current of 0.2C, then charged at a constant voltage of 4.2V until the current value was 0.05C, and discharged to 3.0V with a constant current of 0.2C. Then, in the fourth cycle, the battery was charged to 4.2V with a constant current of 0.2C, then charged at a constant voltage of 4.2V until the current value was 0.05C, and discharged to 3.0V with a constant current of 0.2C to obtain the initial discharge capacity. Then, the battery was charged to 4.2V with a constant current of 0.2C, then charged at a constant voltage of 4.2V until the current value was 0.05C, and the initial resistance was measured. Here, 1C represents the current value at which the battery's standard capacity is discharged in one hour, 5C represents five times that current value, 0.1C represents 1 / 10 of that current value, and 0.2C represents 1 / 5 of that current value.

[0147] [High temperature storage test] After the initial characteristic evaluation, the wound laminate battery was stored at a high temperature of 85° C. for 36 hours. After the battery was cooled sufficiently, the volume of the battery was measured by the Archimedes method, and the gas amount change rate was calculated from the volume change before and after high-temperature storage according to the following formula. Next, the battery was discharged at 0.5C to 3V at 25°C, and the remaining capacity after high-temperature storage was calculated, and the high-temperature storage capacity retention rate (%) was calculated based on the following formula. After charging to 4.2V at a constant current of 0.2C, charging was performed at a constant voltage of 4.2V until the current value reached 0.05C, and then discharging to 3V at 0.5C. After that, charging was performed at a constant current of 0.2C to 4.2V, and charging was performed at a constant voltage of 4.2V until the current value reached 0.05C, and the resistance after high-temperature storage was measured, and the resistance increase rate (%) was calculated based on the following formula. High temperature storage capacity retention rate (%) = (residual capacity) / (initial discharge capacity) x 100 Resistance increase rate (%) = (resistance after high temperature storage (Ω)) / (initial resistance (Ω)) x 100 Gas volume change rate (%) = (volume after high temperature storage (ml)) / (volume before high temperature storage (ml)) x 100

[0148] <Examples 2 to 13 and Comparative Examples 1 to 4> A positive electrode mixture was prepared in the same manner as in Example 1, except that the binder was appropriately dissolved so that the binder solution concentration was 5 to 8 mass %, and the type of binder, the type of conductive assistant, the composition ratio, etc. were changed as shown in each table. Then, a positive electrode was produced using the obtained positive electrode mixture, and evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2. <Comparative Example 5> A water dispersion of the fluorine-containing copolymer (c) was sprayed onto NMC622 and dried to prepare composite NMC622. This composite NMC622 was used as a positive electrode active material to prepare a positive electrode mixture in the same manner as in Example 1. Then, a positive electrode was prepared using the obtained positive electrode mixture and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0149] In each table, "AB+CNT" indicates that acetylene black and multi-walled carbon nanotubes were used as conductive additives, and "AB+graphene" indicates that acetylene black and graphene were used as conductive additives.

[0150] In each table, the "Active material / conductive assistant / binder (wt%)" column shows the content ratio of the positive electrode active material, conductive assistant, and binder relative to the total mass of the positive electrode active material, conductive assistant, and binder in the positive electrode mixture. In addition, when the positive electrode mixture contains two types of conductive assistants, the content ratio of each conductive assistant in the positive electrode mixture is separately shown. For example, the description of "96.9 / 1.2 / 0.4 / 1.5" in Example 1 means that the positive electrode mixture contains 96.9 mass% of the positive electrode active material, 1.2 mass% of acetylene black, 0.4 mass% of multi-walled carbon nanotubes, and 1.5 mass% of the binder relative to the total mass of the positive electrode active material, conductive assistant, and binder.

[0151] <Example 14> (Preparation of Positive Electrode Mixture) The fluorine-containing copolymer (a) as a binder was dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a fluorine-containing copolymer (a) solution with a concentration of 8% by mass. The fluorine-containing copolymer (a) solution, NMC811 as a positive electrode active material, acetylene black (AB) as a conductive assistant, and multi-walled carbon nanotubes (CNT) were mixed using a stirrer to obtain a mixed solution having the composition ratio (active material / conductive assistant / binder) shown in Table 3. NMP was further added to the obtained mixed solution and mixed to prepare a positive electrode mixture with a solid content concentration of 71% by mass.

[0152] (Preparation of positive electrode) The obtained positive electrode mixture was evenly applied to one side of a positive electrode current collector (aluminum foil having a thickness of 20 μm). After the NMP was completely evaporated, the resultant was pressed using a roll press machine at a pressure of 10 tons to produce a positive electrode including a positive electrode mixture layer and a positive electrode current collector. Table 3 shows the amount of positive electrode mixture applied per side, the thickness of the positive electrode mixture layer per side in the positive electrode, the density of the positive electrode mixture layer, and the adhesion of the positive electrode mixture layer to the positive electrode current collector.

[0153] (Preparation of NMC811 laminated cell) The prepared positive electrode was cut to 500mm x 700mm (with positive electrode terminal), and the strip-shaped negative electrode was cut to 502mm x 702mm (with negative electrode terminal), and a lead body was welded to each terminal. In addition, a 20μm thick polypropylene film separator was cut to a size of 504mm x 800mm, and the positive electrode and negative electrode were wound so as to sandwich the separator and placed in a packaging material. Next, 5g of electrolyte (LiPF6 dissolved at a concentration of 1 mol / liter in a solvent mixed with ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3 / 7) was placed in the packaging material and sealed to prepare a wound laminate battery.

[0154] <Evaluation of battery characteristics> The high-temperature storage capacity retention rate, resistance increase rate, and gas amount change rate of the wound laminate battery produced in Example 14 were measured by the following methods. The results are shown in Table 3.

[0155] [Initial Characterization] The wound laminate battery was sandwiched between plates and pressed, and then charged to 4.1V at 25°C with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was repeated for two cycles to stabilize the battery, and in the third cycle, the battery was charged to 4.1V with a constant current of 0.2C, then charged at a constant voltage of 4.1V until the current value was 0.05C, and discharged to 3.0V with a constant current of 0.2C. Then, in the fourth cycle, the battery was charged to 4.1V with a constant current of 0.2C, then charged at a constant voltage of 4.1V until the current value was 0.05C, and discharged to 3.0V with a constant current of 0.2C to obtain the initial discharge capacity. Then, the battery was charged to 4.1V with a constant current of 0.2C, then charged at a constant voltage of 4.1V until the current value was 0.05C, and the initial resistance was measured. Here, 1C represents the current value at which the battery's standard capacity is discharged in one hour, 5C represents five times that current value, 0.1C represents 1 / 10 of that current value, and 0.2C represents 1 / 5 of that current value.

[0156] [High temperature storage test] After the initial characteristic evaluation, the wound laminate battery was stored at a high temperature of 70° C. for 96 hours. After the battery was cooled sufficiently, the volume of the battery was measured by the Archimedes method, and the gas amount change rate was calculated from the volume change before and after high-temperature storage according to the following formula. Next, the battery was discharged at 0.5C to 3V at 25°C, and the remaining capacity after high-temperature storage was calculated, and the high-temperature storage capacity retention rate (%) was calculated based on the following formula. After charging to 4.1V at a constant current of 0.2C, charging was performed at a constant voltage of 4.1V until the current value reached 0.05C, and then discharging to 3V at 0.5C. After that, charging was performed at a constant current of 0.2C to 4.1V, and charging was performed at a constant voltage of 4.1V until the current value reached 0.05C, and the resistance after high-temperature storage was measured, and the resistance increase rate (%) was calculated based on the following formula. High temperature storage capacity maintenance rate (%) = (residual capacity) / (initial discharge capacity) × 100 Resistance increase rate (%) = (resistance after high temperature storage (Ω)) / (initial resistance (Ω)) x 100 Gas volume change rate (%) = (volume after high temperature storage (ml)) / (volume before high temperature storage (ml)) x 100

[0157] <Examples 15 to 26 and Comparative Examples 6 to 9> A positive electrode mixture was prepared in the same manner as in Example 14, except that the binder was appropriately dissolved so that the binder solution concentration was 5 to 8 mass %, and the type of binder, the type of conductive assistant, the composition ratio, etc. were changed as shown in each table. Then, a positive electrode was produced using the obtained positive electrode mixture, and evaluated in the same manner as in Example 14. The results are shown in Tables 3 and 4. <Comparative Example 10> A water dispersion of the fluorine-containing copolymer (c) was sprayed onto NMC811 and dried to prepare composite NMC811. This composite NMC811 was used as a positive electrode active material to prepare a positive electrode mixture in the same manner as in Example 14. Then, a positive electrode was prepared using the obtained positive electrode mixture and evaluated in the same manner as in Example 14. The evaluation results are shown in Table 4. <Example 27> (Preparation of Positive Electrode Mixture) The fluorine-containing copolymer (a) as a binder was dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a fluorine-containing copolymer (a) solution with a concentration of 8% by mass. The fluorine-containing copolymer (a) solution, NCA as a positive electrode active material, acetylene black (AB) as a conductive assistant, and multi-walled carbon nanotubes (CNT) were mixed using a stirrer to obtain a mixed solution having the composition ratio (active material / conductive assistant / binder) shown in Table 5. NMP was further added to the obtained mixed solution and mixed to prepare a positive electrode mixture with a solid content concentration of 71% by mass.

[0158] (Preparation of positive electrode) The obtained positive electrode mixture was evenly applied to one side of a positive electrode current collector (aluminum foil having a thickness of 20 μm). After the NMP was completely evaporated, the resultant was pressed using a roll press machine at a pressure of 10 tons to produce a positive electrode including a positive electrode mixture layer and a positive electrode current collector. Table 5 shows the amount of positive electrode mixture applied per side, the thickness of the positive electrode mixture layer per side in the positive electrode, the density of the positive electrode mixture layer, and the adhesion of the positive electrode mixture layer to the positive electrode current collector.

[0159] (Preparation of NCA laminated cell) The prepared positive electrode was cut to 500mm x 700mm (with positive electrode terminal), and the strip-shaped negative electrode was cut to 502mm x 702mm (with negative electrode terminal), and a lead body was welded to each terminal. In addition, a 20μm thick polypropylene film separator was cut to a size of 504mm x 800mm, and the positive electrode and negative electrode were wound so as to sandwich the separator and placed in a packaging material. Next, 5g of electrolyte (LiPF6 dissolved at a concentration of 1 mol / liter in a solvent mixed with ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3 / 7) was placed in the packaging material and sealed to prepare a wound laminate battery.

[0160] <Evaluation of battery characteristics> The high-temperature storage capacity retention rate, resistance increase rate, and gas amount change rate of the wound laminate battery produced in Example 27 were measured by the following methods. The results are shown in Table 5.

[0161] [Initial Characterization] The wound laminate battery was sandwiched between plates and pressed, and then charged to 4.0V at 25°C with a constant current equivalent to 0.2C, and then discharged to 3.0V with a constant current of 0.2C. This was repeated for two cycles to stabilize the battery, and in the third cycle, the battery was charged to 4.0V with a constant current of 0.2C, then charged at a constant voltage of 4.0V until the current value was 0.05C, and discharged to 3.0V with a constant current of 0.2C. Then, in the fourth cycle, the battery was charged to 4.0V with a constant current of 0.2C, then charged at a constant voltage of 4.0V until the current value was 0.05C, and discharged to 3.0V with a constant current of 0.2C to obtain the initial discharge capacity. Then, the battery was charged to 4.0V with a constant current of 0.2C, then charged at a constant voltage of 4.0V until the current value was 0.05C, and the initial resistance was measured. Here, 1C represents the current value at which the battery's standard capacity is discharged in one hour, 5C represents five times that current value, 0.1C represents 1 / 10 of that current value, and 0.2C represents 1 / 5 of that current value.

[0162] [High temperature storage test] After the initial characteristic evaluation, the wound laminate battery was stored at high temperature for 720 hours at 60° C. After the battery was cooled sufficiently, the volume of the battery was measured by Archimedes' method, and the gas amount change rate was calculated from the volume change before and after high-temperature storage according to the following formula. Next, the battery was discharged at 0.5C to 3V at 25°C, and the remaining capacity after high-temperature storage was calculated, and the high-temperature storage capacity retention rate (%) was calculated based on the following formula. After charging to 4.0V at a constant current of 0.2C, charging was performed at a constant voltage of 4.0V until the current value reached 0.05C, and then discharging to 3V at 0.5C. After that, charging was performed at a constant current of 0.2C to 4.0V, and charging was performed at a constant voltage of 4.0V until the current value reached 0.05C, and the resistance after high-temperature storage was measured, and the resistance increase rate (%) was calculated based on the following formula. High temperature storage capacity maintenance rate (%) = (residual capacity) / (initial discharge capacity) × 100 Resistance increase rate (%) = (resistance after high temperature storage (Ω)) / (initial resistance (Ω)) x 100 Gas volume change rate (%) = (volume after high temperature storage (ml)) / (volume before high temperature storage (ml)) x 100

[0163] <Examples 28 to 39 and Comparative Examples 11 to 14> A positive electrode mixture was prepared in the same manner as in Example 27, except that the binder was appropriately dissolved so that the binder solution concentration was 5 to 8 mass%, and the type of binder, the type of conductive assistant, the composition ratio, etc. were changed as shown in each table. Then, a positive electrode was produced using the obtained positive electrode mixture, and evaluated in the same manner as in Example 27. The results are shown in Tables 5 and 6. <Comparative Example 15> A composite NCA was prepared by spraying an aqueous dispersion of the fluorine-containing copolymer (c) onto NCA and drying it. A positive electrode mixture was prepared in the same manner as in Example 27 using this composite NCA as a positive electrode active material. A positive electrode was then prepared using the obtained positive electrode mixture and evaluated in the same manner as in Example 27. The evaluation results are shown in Table 6.

[0164] [Table 1]

[0165] [Table 2]

[0166] [Table 3]

[0167] [Table 4]

[0168] [Table 5]

[0169] [Table 6] < / pvdf>

Claims

1. An electrode mixture containing a lithium-containing transition metal oxide, a conductive assistant, a binder, and an organic solvent, The conductive assistant contains at least one nanocarbon material selected from the group consisting of multi-walled carbon nanotubes and graphene, The electrode mixture, wherein the binder contains a fluorine-containing copolymer containing vinylidene fluoride units and fluorinated monomer units (excluding vinylidene fluoride units), and the content of the vinylidene fluoride units in the fluorine-containing copolymer is 57.0 mol % or more and 97.0 mol % or less based on the total monomer units.

2. The electrode mixture according to claim 1 , wherein the fluorinated monomer unit is a tetrafluoroethylene unit.

3. 3. The electrode mixture according to claim 1, wherein the content of the binder is 0.3 to 3.0 mass% with respect to the total mass of the lithium-containing transition metal oxide, the conductive assistant, and the binder.

4. The electrode mixture according to any one of claims 1 to 3, wherein the content of the conductive assistant is 0.3 to 3.0 mass% with respect to the total mass of the lithium-containing transition metal oxide, the conductive assistant and the binder.

5. 5. The electrode mixture according to claim 1, wherein the binder further contains polyvinylidene fluoride.

6. An electrode comprising: a current collector; and an electrode mixture layer provided on one or both sides of the current collector and formed from the electrode mixture according to any one of claims 1 to 5.

7. A secondary battery comprising the electrode according to claim 6.

Citation Information

Patent Citations

  • Negative electrode material for lithium polymer battery, negative electrode using the same, lithium ion battery and lithium polymer battery using negative electrode

    JP2004220911A

  • Positive electrode for secondary batteries, and secondary battery

    JP2015109154A

  • Positive electrode mixture slurry, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2017182989A

  • Binder for secondary battery and electrode mixture for secondary battery

    JP2018060745A

  • Binder for secondary battery and electrode mixture for secondary battery

    JP2018063932A